Risk of Coronary Heart Disease among HIV-Infected Patients: A Multicenter Study in Brazil - Sandra C. Fuchs; Paulo R. Alencastro; Maria Letícia R. Ikeda; Nêmora T. Barcellos; Fernando H. Wolff; Ajácio B. M. Brandão; Ricardo A. A. Ximenes; Demócrito de B. Miranda-Filho; Heloísa Ramos Lacerda; Maria de Fátima P. M. de Albuquerque; Ulisses Ramos Montarroyos; Max W. Nery; et al. (The Scientific World Journal)
Cardiovascular disease has emerged as a crescent problem among HIV-infected population. This study aimed to determine the 10-year risk of coronary heart disease using the Framingham risk score among HIV-infected patients from three regions of Brazil. This is a pooled analysis of three cohort studies, which enrolled 3,829 individuals, 59% were men, 66% had white skin color, and mean age 39.0 ± 9.9 years. Comparisons among regions showed that there were marked differences in demographic, socioeconomic, clinical, and HIV-related characteristics. Prevalence of Framingham score ≥10 was 4.5% in the Southern, 4.2% in the Midwest, and 3.9% in the Northeast of Brazil. The Framingham score ≥10 was similar between regions for males, patients aged ≥60 years, with obesity, central obesity, hypertension, and diabetes mellitus. Women were three times more likely to have coronary heart disease in 10 years than men. Hypertension and diabetes increased more than four times the risk of coronary heart disease, followed by central obesity, obesity, and prehypertension. The use of antiretroviral agents and time since HIV diagnosis were not risk factors for coronary artery disease in 10 years. In conclusion, hypertension and diabetes are the strongest independent predictors of 10-year risk of coronary heart disease among HIV-infected population.